How Colposcopy Misses Invasive Cervical Cancer: A Case Report from the IMPROVE-COLPO Study - Jeff Livingston; Emmanouil Papagiannakis (Hindawi Limited, 2016)
Colposcopy with biopsy is pivotal to cervical cancer prevention programs as it is called to identify the precancerous lesions on patients that screen positive. We present a cervical cancer case from IMPROVE-COLPO, a postmarketing, multicenter, two-arm observational study on US community colposcopy that collects outcomes with the adjunctive Dynamic Spectral Imaging (DSI) in its prospective arm. A 45-year-old woman was seen for suffering of heavy periods. She had cytology of Atypical Squamous Cells of Undetermined Significance (ASC-US) and was Human Papillomavirus (HPV) positive. Her colposcopy did not recognize the underlying condition and opted for no biopsy. The DSI assessment led to a biopsy of a lesion challenging traditional colposcopic templates: small, away from the cervical os, with slow acetowhitening development. Pathology review revealed the presence of invasive squamous carcinoma. In the era of sensitive screening, it is concerning that invasive cancers can challenge colposcopy and that the way to improve colposcopy is to collect multiple biopsies from each patient. The case presented indicates that the adjunctive objective assessment by DSI increases reassurance that observations outside of traditional standard visual templates are not underestimated or ignored.